Evolution entropy risk assessment of ERP information security based on the business process - Biao SONG; Jian-ming ZHU (Tongxin xuebao)
ERP internal security holes often bind with business process closely,make the value of information assets has dynamic properties and difficult to determined,so such security will not be prompt capture and evaluation.Compored the difference of ERP system and other information system in the information security,the risk assessment model which adapt to the characteristics of ERP system was proposed,and gave a new idea for the ERP system information safety risk assessment.